Question: how to split Sum seriers

I have got an equation of Sum.i want to split the eqution three parts of Sum,how can do?

ans:=sum(I*`ℏ`*(diff(c[n](t), t))*phi(r)*exp(-I*omega[n]*t)-(1/2)*E[0](e_.r_)*e*c[n](t)*phi(r)*omega[n]*exp(-I*omega[n]*t+I*Omega*t)-(1/2)*E[0](e_.r_)*e*c[n](t)*phi(r)*omega[n]*exp(-I*omega[n]*t-I*Omega*t), n = l .. k)

i want to  result like this

ans1:=sum(I*'ℏ'*(diff(c[n](t), t))*phi(r)*exp(-I*omega[n]*t), n = l .. k) = sum((1/2)*E[0](e_.r_)*e*c[n](t)*phi(r)*omega[n]*exp(-I*omega[n]*t+I*Omega*t), n = l .. k)+sum((1/2)*E[0](e_.r_)*e*c[n](t)*phi(r)*omega[n]*exp(-I*omega[n]*t-I*Omega*t), n = l .. k)

thanks a lot in advance.
Please Wait...